Effect of foliar application of microelements on chlorophyll content, canopy architecture indicators, and physiological parameters of Hordeum vulgare L. plants - Stadnik, Barbara; Tobiasz-Salach, Renata; Migut, Dagmara (PeerJ, 2025)
Background The availability of nutrients determines the proper development and yield of plants. Microelements play an important role primarily as cofactors of important enzymes in the metabolic and physiological processes of plants. Barley (Hordeum vulgare L.) is one of the most popular cereals in the world. It is used mainly as animal feed and as a raw material for the brewing industry. Methods A three-year field experiment was conducted to determine the effect of foliar spraying of plants with single-component fertilizers containing copper, manganese, molybdenum, and zinc on the physiological parameters of barley plants. In the experiment, three malting barley cultivars were tested: Baryłka, KWS Irina, RGT Planet. During the vegetation period of the plants after foliar fertilization, canopy architecture indices, chlorophyll content in leaves, and gas exchange and chlorophyll fluorescence parameters were measured. Results The foliar application of each of the microelements tested caused a significant increase in the chlorophyll content in the leaves and canopy architecture parameters (LAI and MTA) compared to the control. Furthermore, a significant increase in gas exchange parameters was also observed: intercellular CO2 concentration (Ci), transpiration rate (E), stomatal conductance (gs), net photosynthetic rate (PN) and chlorophyll fluorescence parameters, maximum quantum yield of PSII photochemistry (Fv/Fm), fraction of active PSII reaction centers (RC/ABS), potential photochemical efficiency (Fv/F0), and performance index (PI). The highest results of physiological parameters such as CCI, Ci, E, Fv/Fm, Fv/F0 and PI were recorded after the application of zinc fertilizer. LAI and MTA were highest in plots with plants sprayed with molybdenum-based fertilizer. The foliar application of Cu caused the greatest increase in Ci and PN. The experiment showed significant genotypic differences. The RGT Planet cultivar had a higher chlorophyll content, E and PN parameters among the tested cultivars. The KWS Irina cultivar was characterized by the highest values of canopy architecture parameters and significantly lower values of CCI, Fv/Fm and Fv/F0 compared to the Baryłka and RGT Planet.
Keywords: Barley; Chlorophyll fluorescence; Foliar fertilization; Gas exchange; Microelement fertilizer